Current Infectious Disease Reports - Slama, Thomas G.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
This journal intends to provide clear, insightful, balanced contributions by international experts that review the most important, recently published clinical findings related to the diagnosis, treatment, management, and prevention of infectious disease. We accomplish this aim by appointing international authorities to serve as Section Editors in key subject areas, such as HIV/AIDS, sexually transmitted diseases, tropical and travel medicine, and urinary tract infections. Section Editors, in turn, select topics for which leading experts contribute comprehensive review articles that emphasize new developments and recently published papers of major importance, highlighted by annotated reference lists. An international Editorial Board reviews the annual table of contents, suggests articles of special interest to their country/region, and ensures that topics are current and include emerging research. Commentaries from well-known figures in the field are also provided.
Keywords: Infectious diseases; Infectious Diseases